Tingkat Kecemasan Pasien Kardiovaskuler pada Masa Pandemi COVID-19 - Juli Andri; Padila Padila; Nur Afni Wulandari Arifin (Journal of Telenursing (JOTING), 2021)
This study aims to determine the level of anxiety of patients with cardiovascular disorders during the COVID-19 pandemic in the work area of the Telaga Dewa Health Center, Bengkulu City. The type of research used in this research is quantitative research with a cross-sectional approach. The results showed that the level of anxiety of respondents who were included in the standard/not anxious category was 4 respondents (5.4%), mild anxiety was 27 respondents (36.5%), moderate anxiety was 33 respondents (44.6%), and anxious weight as many as 10 respondents (13.5%). In conclusion, the anxiety level of patients with cardiovascular disorders during the COVID-19 pandemic in the Telaga Dewa Health Center work area, Bengkulu City, was in the moderate anxiety category. Keywords: COVID-19, Cardiovascular, Anxiety Level